2006
DOI: 10.1055/s-2006-926412
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to C-Trimethylsilyl-1,3-azoles

Abstract: Direct silylation of 1,3-azoles with bromotrimethylsilane in the presence of triethylamine was investigated. 5-Phenyloxazole, benzoxazole, 1-methyl-1,2,4-triazole, 2-aryl-1,3,4-oxa-and thiadiazoles were found to give the corresponding 2-or 5-trimethylsilyl derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Presumably, N-acylation is followed by deprotonation of the acidic C-2 proton and subsequent acyl migration affords the final product. Silylations under similar conditions have also been successful 5. Finally, Kondo has shown that electron-rich and electron-deficient arenes can be functionalized by employing t Bu-P4 base/non-enolizable ketone and aldehyde mixtures 6…”
Section: Introductionmentioning
confidence: 97%
“…Presumably, N-acylation is followed by deprotonation of the acidic C-2 proton and subsequent acyl migration affords the final product. Silylations under similar conditions have also been successful 5. Finally, Kondo has shown that electron-rich and electron-deficient arenes can be functionalized by employing t Bu-P4 base/non-enolizable ketone and aldehyde mixtures 6…”
Section: Introductionmentioning
confidence: 97%
“…Thus, the attempt to synthesize N ‐silyltriazolylidenes from the corresponding N ‐silyltriazolium salts led to C ‐silyltriazoles , . The reaction of bromotrimethylsilane with a set of nitrogen‐containing heterocycles directly led to C ‐silylated derivatives, which were most likely formed by the carbene mechanism . C ‐Silylformamidines 3 are colorless, crystalline compounds that are extremely moisture‐sensitive.…”
Section: Resultsmentioning
confidence: 99%
“…N-Methyl-NЈ-trimethylsilylimidazolium Bromide (1; MTMSImBr): [45] N-Methylimidazole (17.9 g, 0.2 mol) was slowly added dropwise to a solution of bromotrimethylsilane (33.4 g, 0.2 mol) in dry diethyl ether (100 mL) under Ar at 0°C. The resulting white precipitate was filtered off washed thoroughly with diethyl ether and finally dried in vacuo at ambient temperature.…”
Section: Methodsmentioning
confidence: 99%